Randomized trial on extended versus modified right lobe grafts in living donor liver transplantation. Issue 7 (23rd July 2018) - Varghese, Christi Titus; Bharathan, Viju Kumar; Gopalakrishnan, Unnikrishnan; Balakrishnan, Dinesh; Menon, Ramachandran N.; Sudheer, Othiyil Vayoth; Dhar, Puneet; Sudhindran, Surendran
Abstract : Despite advances in the practice of living donor liver transplantation (LDLT), the optimum surgical approach with respect to the middle hepatic vein (MHV) in right lobe LDLT remains undefined. We designed a randomized trial to compare the early postoperative outcomes in recipients and donors between extended right lobe grafts (ERGs; transection plane was maintained to the left of MHV and division of MHV performed beyond the segment VIII vein) and modified right lobe grafts (MRGs; transection plane was maintained to the right of MHV; the segment V and VIII drainage was reconstructed using a conduit of recipient portal vein). Eligible patients (n = 86) were prospectively randomized into the ERG arm (n = 43) and the MRG arm (n = 43) at the beginning of donor hepatectomy. The primary endpoint considered in this equivalence trial was patency of the MHV or the reconstructed "neo‐MHV" in the recipient. The secondary endpoints included biochemical parameters, postoperative complications, mortality in recipients as well as donors and volume regeneration of remnant liver in donors, measured at 2 months. The patency of the MHV was comparable in the ERG and MRG arms (90.7% versus 81.4%; difference, 9.3%; 95% confidence interval [CI], –5.8 to 24.4; z score, 1.245; P = 0.21). Volume regeneration of the remnant liver in donors was significantly better in the MRG arm (111.3% versus 87.3%; mean difference, 24%; 95% CI, 14.6‐33.3; P < 0.001). The remaining secondary endpoints in donors and recipients were similar between the 2 arms. To conclude, MRG with reconstructed neo‐MHV has comparable patency to native MHV in ERG and confers equivalent graft outflow in the recipient. Furthermore, it allows better remnant liver regeneration in the donor at 2 months. Liver Transplantation 24 888–896 2018 AASLD.